Immunological Profile of Patients with Controlled and Uncontrolled Type 2 Diabetes Melitus in Mataram City, West Nusa Tenggara - Arjita, I Putu Dedy; Adnyana , I Gede Angga; Anulus, Ayu; Saputra, I Putu Bayu Agus; Diarti, Maruni Wiwin (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
The prevalence of DM disease in West Nusa Tenggara Province is not much different from that in Indonesia. DM cases in NTB are included in the ten most non-communicable illnesses suffered by the community and the incidence continues to increase from year to year. An increase in the levels of pro-inflammatory cytokines in the body is one of the causes of insulin resistance in cells which can further develop into type 2 diabetes. This study involved diabetic patients at the Mataram Community Health Center, who were assigned into 2 groups, namely the controlled diabetes group and the uncontrolled diabetes group and involved a standard group which was a group consisted of healthy people. Each group was examined for Fasting Blood Glucose (FBG) and HbA1c levels. The results of the examination in the standard group, controlled diabetes group and uncontrolled diabetes group obtained the FBG levels of 89.22 mg/dl, 110.0 mg/dl, and 245.80 mg/dl, respectively. Furthermore, the results of the HbA1c test in the standard group, controlled diabetes group and uncontrolled diabetes group were 5.44%, 6.03%, and 10.49%, respectively. The results of the examination of IL-6 levels in the standard group, controlled diabetes group and uncontrolled diabetes were 329.36 pg/ml, 331.52 pg/ml, and 320.33 pg/ml, respectively. The results of the IL-10 test in the standard group, controlled diabetes group and uncontrolled diabetes were 71.80 pg/ml, 116.60 pg/ml, and 128.10 pg/ml, respectively. Based on the results of the study, there was no significant difference in the levels of interleukin 6 and interleukin 10 between respondents with diabetes mellitus and healthy respondents (p>0.05). It can be concluded that there were no differences in interleukin 6 and 10 levels between healthy people with patients with controlled and uncontrolled diabetes.